Brewing By-Products as a Source of Natural Antioxidants for Food Preservation - Idoia Codina-Torrella; Lourdes Rodero; María Pilar Almajano (MDPI AG, 2021)
Brewer's spent grain (BSG) and brewer's spent hops (BSH) are the major solid by-products of the brewing industry. The present work evaluated their potential as an alternative source of natural antioxidants. The efficacy of different solvents (MilliQ water, 0.75% NaOH, 50% MeOH, 50% MeOH + 0.3% HCl and 50% Acetone) for extracting polyphenols of these by-products was firstly evaluated, with NaOH showing the best results. The extraction conditions were optimized using the response surface methodology, and were determined to be 1.45% NaOH and 80 °C. BSG extracts showed the highest total polyphenol content (24.84-38.83 µmol GAE/g), whereas the BSH showed the lowest value (24.84 ± 1.55 µmol GAE/g). In general, BSG extracts presented significantly higher antioxidant capacity (ABTS, ORAC). Ferulic acid was the main polyphenol in all BSG extracts (156.55-290.88 mg/100 g), whereas in BSH, this compound was not detected. The addition of 10% BSG extract in o/w emulsions (stored 14 days) showed a reduction in the formation of primary oxidation products of 97%. In the emulsions covered with polylactic acid active films (1% BSG), this reduction corresponded to 35%. Hence, this study demonstrates the potential of these by-products as natural antioxidant sources for protecting food systems against oxidation.